2021
DOI: 10.1016/j.esmoop.2021.100241
|View full text |Cite
|
Sign up to set email alerts
|

Baseline neutrophil-to-lymphocyte ratio as a predictive and prognostic biomarker in patients with metastatic castration-resistant prostate cancer treated with cabazitaxel versus abiraterone or enzalutamide in the CARD study

Abstract: Background There is growing evidence that a high neutrophil-to-lymphocyte ratio (NLR) is associated with poor overall survival (OS) for patients with metastatic castration-resistant prostate cancer (mCRPC). In the CARD study (NCT02485691), cabazitaxel significantly improved radiographic progression-free survival (rPFS) and OS versus abiraterone or enzalutamide in patients with mCRPC previously treated with docetaxel and the alternative androgen-receptor-targeted agent (ARTA). Here, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…In the docetaxel-treated group, we found that the NLR at baseline and at 12 weeks was not associated with OS. Even if our findings are consistent with Sumbul et al and Linton et al [ 19 , 20 ], many other studies have shown, for different NLR cut-offs, that the NLR ratio was associated with longer OS in chemotherapy-treated patients [ 3 , 18 , 21 , 22 , 23 ]. This difference in our patients could be explained by a lack of statistical power and the fact that prostate cancer is considered an immunologically cold cancer [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the docetaxel-treated group, we found that the NLR at baseline and at 12 weeks was not associated with OS. Even if our findings are consistent with Sumbul et al and Linton et al [ 19 , 20 ], many other studies have shown, for different NLR cut-offs, that the NLR ratio was associated with longer OS in chemotherapy-treated patients [ 3 , 18 , 21 , 22 , 23 ]. This difference in our patients could be explained by a lack of statistical power and the fact that prostate cancer is considered an immunologically cold cancer [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…Despite, the therapeutic progress made recently, life expectancy remains poor. A better understanding of the predicting treatment response is needed to optimize the use and the sequencing of available therapies [ 3 ]. Lymphocytes and neutrophils have been implicated in host immune response to cancer including prostate cancer, either as a factor of host defense or tolerance [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the resulting Cox proportional hazards models, all factors previously identified by the Bellmunt model, that is, ECOG PS, hemoglobin and liver metastases, were independent predictors of survival. TFLC, previously identified as an important prognostic factor, 12 ALP, bone metastases and NLR were also retained in both models. Tumor–node–metastases stage at diagnosis was not retained in the model without PD-L1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the cut-off defining low versus high NLR differs from previous publications and might be considered arbitrary. 15,24,[46][47][48] However, there is no clear consensus regarding the optimal cut-off. There are numerous studies and meta-analyses conducted in prostate cancer investigating the prognostic value of NLR across the whole spectrum of the disease.…”
Section: Discussionmentioning
confidence: 99%